Autosomal dominant tubulointerstitial kidney disease (ADTKD) in Ireland. (1st January 2019) - Cormican, S.; Connaughton, D. M.; Kennedy, C.; Murray, S.; Živná, M.; Kmoch, S.; Fennelly, N. K.; O'Kelly, P.; Benson, K. A.; Conlon, E. T.; Cavalleri, G.; Foley, C.; et al.
Abstract: Introduction: Autosomal dominant tubulointerstitial kidney disease (ADTKD) is a rare genetic cause of renal impairment resulting from mutations in the MUC1, UMOD, HNF1B, REN, and SEC61A1 genes. Neither the national or global prevalence of these diseases has been determined. We aimed to establish a database of patients with ADTKD in Ireland and report the clinical and genetic characteristics of these families. Methods: We identified patients via the Irish Kidney Gene Project and referral to the national renal genetics clinic in Beaumont Hospital who met the clinical criteria for ADTKD (chronic kidney disease, bland urinary sediment, and autosomal dominant inheritance). Eligible patients were then invited to undergo genetic testing by a variety of methods including panel-based testing, whole exome sequencing and, in five families who met the criteria for diagnosis of ADTKD but were negative for causal genetic mutations, we analyzed urinary cell smears for the presence of MUC1fs protein. Results: We studied 54 individuals from 16 families. We identified mutations in the MUC1 gene in three families, UMOD in five families, HNF1beta in two families, and the presence of abnormal MUC1 protein in urine smears in three families (one of which was previously known to carry the genetic mutation). We were unable to identify a mutation in 4 families (3 of whom also tested negative for urinary MUC1fs). Conclusions: There are 4443 people with ESRD in Ireland, 24 of whom are members of the cohort described herein. We observe that ADTKD represents at least 0.54% of Irish ESRD patients.